Influence of the COVID-19 Pandemic on Mood and Training in Australian Community Tennis Players - Turner, Mitchell; Beranek, Philipp; Rogers, Shane L.; Nosaka, Kazunori; Girard, Olivier; Cruickshank, Travis (Frontiers in Sports and Active Living, 2021)
The COVID-19 outbreak has led to the implementation of strict restrictions in Australia, which have severely impacted sporting activities. Tennis is played by 6.2% of the population within the Oceania region, and is a valuable sport for maintaining social, mental, and physical health. Current literature indicates the COVID-19 pandemic has negatively affected the mental health of Australian residents. The aim of this study was to investigate changes in training and match play due to the outbreak, and its effects on emotional well-being of Australian senior tennis players. Additionally, explore any differences between middle aged (41–60 years) and senior (61 years and over) Australian tennis players. An online survey was used to assess training and match play habits, as well as ascertain the emotional well-being of tennis players. The survey was active from 24th April 2020 until 6th June 2020. Participants were adult (41+ years) tennis players from Australia. Wilcoxon signed rank tests were performed to check for differences in training hours and tennis matches played. Mann–Whitney U tests were used to assess the difference in Brief Emotional Experience Scale (BEES) scores, employment status as well as the training hours and tennis matches played between the two age groups. A Kendall's Tau B correlation test was performed to assess the associations of training, match play and demographic characteristics with BEES scores. Kruskal–Wallis tests assessed differences in BEES scores between participants of differing match play formats, tennis experience and cessation of tennis training time periods. There were 245 respondents who met our inclusion criteria. Tennis training hours along with the tennis matches played significantly decreased during COVID-19 compared to pre-COVID-19, 85.09 and 88.48%, respectively. No significant (p > 0.05) differences were observed between age groups for any of the training modality hours, nor was there any significant difference in number of tennis matches played. The participants average BEES score was 0.99 ± 1.27, indicating that respondents had a positive emotional well-being during the COVID-19 pandemic. The emotional well-being of the senior group was significantly (P = 0.002) higher than the middle aged group. Together, our results show that training and tennis match play decreased during the COVID-19 pandemic, however the emotional well-being of senior tennis players in Australia appeared to not be negatively affected.